Traces of Transhumanism in Michel Houellebecq’s Novel Elementary Particles - Buğra Şengel (Current Perspectives in Social Sciences, 2024)
Transhumanism sees the next step of the evolution of humanity in technology, together with the developments in the twentieth century and the influence of positivism. As a modern repetition of the golem myth, it desires to use technology as o tool for a stronger, smarter, non-sick, even immortal humanity. Transhumanists developed in an environment where the influence of humanism was reduced due to materialism and they aim to create a super human through technologies such as biotechnology, nanotechnology, artificial intelligence and cloning, and tries to bring humans to a higher position. In literature, which is a close follower mirror of social developments, transhumanist works are frequently encountered as they create a suitable environment for the development and discussion of transhumanist ideas. Therefor Transhumanism has become an important subject in world literature and has attracted the attention of French authors, especially with the twenty-first century. Michel Houellebecq, one of the leading figures of contemporary French literature, is famous for deeply processing existential themes and bringing striking subjects such as religion, nudity and the human condition into his novels by refence. His novel Elementary Particles, published in 1998, problematizes the potential return of transhumanist ideas, human desires and technological advances, while depicting a modern society where life has lost its meaning with the advancement of scientific developments. This article aims to reveal the author’s ideas for the future of humanity in a world driven by the increasing use of technology while critically investigating the traces of transhumanism in Houellebecq’s Elementary Particles. After providing an overview of the foundations of the theory by creating a framework for understanding the concept of transhumanism, the study tries to reveal the author’s transhumanist ideas and the potential consequences of transcending human boundaries by making use of important themes and passages in the novel.